JOURNAL "The Effect Of Product Quality, Price, Promotion And Trust To Purchase Decision Process Tile Products "MAHKOTA INDUTRI" In Majalengka - Yanuar, Richo; Sholahuddin Diponegoro Singadimeja, Muhamad; Rachmawati SE.MM, Mariana (International Journal of Psychosocial Rehabilitation, 2020)
The more rapid the development of housing both in cities and villages this also affects the increasing demand for material needs. Seeing this property business opportunity is still quite promising to run. Doing property business is not about having to build a house or make interior or exterior furniture. There is one business opportunity that you can run, namely tile production. This business is able to provide many benefits for you. Roof Tile is a roof covering that serves to protect from heat and rain. Roof tile is an important component for every home. Tile from clay is still the target of many people, because tile from clay is considered more safe and comfortable to use. Conventional tile or clay tile, in terms of shape is a bit outdated, but this tile has the advantage of modern tile. Conventional tile will make the house cooler and healthier even though the room has no sunlight. This becomes a very high business opportunity, therefore more and more competition is also higher among the business of making these tiles. This is what researchers are interested in. to conduct research on the Tile Industry. By title "The Effect of Product Quality, Price, Promotion and Trust on the Purchasing Decision Process of" Mahkota Industri "Tile Products in Majalengka, West Java. The purpose of this research is to find out how much Product Quality, Price, Promotion and Trust influence the Product Purchasing Decision Process, in particular, the population of tile in the "Mahkota Industri" The unit of analysis of this study is consumers and customers of the "Mahkota Industri", with a hypothesis test using Multiple Linear Regression. The results of the research hypothesis: Product quality has a significant positive effect on the purchasing decision process. Price has a significant positive effect on the purchasing decision process. Promotion has a significant positive effect on the purchasing decision process. Trust has a significant positive effect on the purchasing decision process.